WAYS OF EXPRESSING POLITENESS IN DIFFERENT CULTURES - Toshmatov Alimardon Sotvoldiyevich; Madaminova Mashrabxon Shoyatjon qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract. This article explores how different cultures express politeness in various ways. By examining customs and rituals, we uncover the diverse approaches to showing respect and courtesy globally. From subtle gestures in everyday interactions to formalities during ceremonies, each culture offers unique insights into politeness. Understanding these differences help individuals navigate cross-cultural interactions more effectively and promote understanding and respect in our interconnected world.